VDC_100102371237.0X000001. Issue 10 (October 2018) - Russell, Tara A.; Chung, Hallie; Riad, Christina; Reardon, Sarah; Kazanjian, Kevork; Cherry, Robert; Hines, O. Joe; Lin, Anne
Surgical site infections (SSIs) are considered a quality metric across surgical specialties and are a major cause of increased readmissions and overall costs to surgical patients. Bundled interventions have demonstrated efficacy in reducing SSIs in various surgical fields, yet the ability to sustain and spread interventions while continuing to reduce infection rates is a significant challenge. This study assessed the implementation and sustainability of an SSI bundle, which was initially piloted within the colorectal surgery division and then spread to additional general surgery services. Outcomes (risk-adjusted ACS-NSQIP odds ratio and observed to expected (O:E) SSI rates) and process measures were monitored on run charts throughout the course of the intervention. By the end of the study period, ACS-NSQIP risk-adjusted odds ratios for SSIs decreased from 1.22 to 0.95 for colorectal procedure targeted and 1.32 to 1.04 for all general surgery procedures ( P < 0.05). O:E ratios showed similar reductions. SSI reductions were associated with process measure compliance. This study demonstrates that effective implementation within a single surgical division provides the foundation for spread of a SSI bundle, which results in continued and sustained reductions in SSI rates.